Student study guide to accompany Statistics for business and economics - Curl, James C.; Mann, Prem S. (New York ; Chichester : John Wiley and Sons, 1995)
Philosophy of the study guide. Introduction. Organizing data. Numerical descriptive measures. Probability. Discrete random variables and their probability distributions...
Keywords: Commercial statistics; Social sciences; Statistical methods; Statistics -- Problems, exercises, etc; Economics -- Statistical methods; Social sciences -- Statistical methods; Commercial statistics